Physiological and biochemical measurements on juvenile Antarctic rockcod (Trematomus bernacchii) from McMurdo Sound - Davis, Brittany; Flynn, Erin; Miller, Nathan; Todgham, Anne (IEDA: US Antarctic Program Data Center, 2017)
This dataset includes data from the publication \"Davis, et al. (2016) - Juvenile Antarctic rockcod (Trematomus bernacchii) are physiologically robust to CO2-acidified seawater\". Included are data on cardiorespiratory physiology, survival, metabolic rate, metabolic enzyme activity (citrate synthase) and seawater chemistry.